Analysis of Vitamin A in Multivitamin Products - A. S. Alekseeva; T. B. Shemeryankina; M. N. Lyakina; M. S. Smirnova; E. P. Fedorova; S. D. Kakhramanova (Регуляторные исследования и экспертиза лекарственных средств, 2021)
Vitamin A is present in multivitamin products mainly in the form of retinol esters: retinyl acetate, retinyl palmitate, and beta carotene—retinol precursor (dimer) found in plants, which is capable of converting into retinol in liver cells. Retinol is determined in medicinal products primarily by high performance liquid chromatography (HPLC), with preliminary purification and vitamin isolation by liquid-liquid extraction. However, scientific literature also describes other methods of sample preparation and analysis of such compounds. An important issue is differentiation of vitamin A from other fat-soluble vitamins often included as components in multivitamin products. The aim of the study was to analyse and summarise data on current methods used for determination of vitamin A and its derivatives in medicinal products. The authors analysed the range of vitamin A products authorised in the Russian Federation, and the test methods described in their product specification files. The study demonstrated that the test method most often used for determination of retinol esters was HPLC with isocratic elution mode using octadecylsilyl packing in the reverse-phase mode, and, less frequently, aminopropylsilyl packing in the normal phase mode. Determination of beta carotene in medicinal products is most often performed using spectrophotometry.